Stochastic Integrals in Formulating Discounting Models for Implementations of Strategic Operations (Journal of Informatics and Mathematical Sciences, 2023)
In many cases of formulating stochastic models the principal components of such models are stochastic integrals. In consequence, stochastic discounting integrals are used as principal components of stochastic discounting models. The present paper makes use of a positive random variable and a stochastic discounting integral for the formulation of a stochastic discounting model. Moreover, the paper provides interpretation of the formulated stochastic discounting model in developing and investigating strategic operations.